An overview of treatment options for mild‐to‐moderate acne based on American Academy of Dermatology, European Academy of Dermatology and Venereology, and Italian Society of Dermatology and Venereology guidelines. Issue 4 (25th May 2020) - Conforti, Claudio; Chello, Camilla; Giuffrida, Roberta; di Meo, Nicola; Zalaudek, Iris; Dianzani, Caterina
Abstract: Acne is a common inflammatory skin disorder affecting the pilosebaceous unit. Patients with mild‐to‐moderate acne can be treated with a combination of topical, systemic, and physical therapeutic approaches, with different results depending on patient, disease, and treatment characteristics. Herein we describe and discuss the common and alternative treatment options used for mild‐to‐moderate acne, by comparing three widely distributed guidelines (American Academy of Dermatology, European Academy of Dermatology and Venereology, and Italian Society of Dermatology and Venereology.